1997
DOI: 10.5951/mt.90.5.0344
|View full text |Cite
|
Sign up to set email alerts
|

Issues and Aids for Teaching Mathematics to the Blind

Abstract: Efforts at inclusion and mainstreaming are pervasive in classrooms across North America. One of the many special populations formerly segregated but currently mainstreamed includes blind or partially sighted students. In this article we discuss some of the challenges faced by blind and visually impaired students and some of the tools available to help these students in their efforts to learn mathematics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
6

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 0 publications
1
17
0
6
Order By: Relevance
“…Earlier exposure to such ---technology can benefit students in terms of familiarity and ease of use (Prensky, 2001). Additionally, as found in this study and noted in the literature, textbook instruction drives mathematics teaching, yet textbooks often are not considerate of students with visual impairments (Dick & Kubiak, 1997;Tyson & Woodward, 1989). Supported eText reduces reliance on printed text and its challenges (i.e., enough large-print copies, the number of volumes, and lack of color), and standardizes the presentation of mathematics in a consistent language (i.e., x=(a/b)+1 presented as x equals BEGIN FRACTION a OVER b END FRACTION plus 1, without ambiguity for interpretation; Landau, Russell, Gourgey, Erin, & Cowan, 2003;MacGregor & Price, 1999;Raman, 1994).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Earlier exposure to such ---technology can benefit students in terms of familiarity and ease of use (Prensky, 2001). Additionally, as found in this study and noted in the literature, textbook instruction drives mathematics teaching, yet textbooks often are not considerate of students with visual impairments (Dick & Kubiak, 1997;Tyson & Woodward, 1989). Supported eText reduces reliance on printed text and its challenges (i.e., enough large-print copies, the number of volumes, and lack of color), and standardizes the presentation of mathematics in a consistent language (i.e., x=(a/b)+1 presented as x equals BEGIN FRACTION a OVER b END FRACTION plus 1, without ambiguity for interpretation; Landau, Russell, Gourgey, Erin, & Cowan, 2003;MacGregor & Price, 1999;Raman, 1994).…”
Section: Discussionsupporting
confidence: 55%
“…Tyson and Woodward (1989) suggested that 75-90% of mathematics instruction in a standard classroom is based on the mathematics textbook; yet, textbooks are seldom designed for students with disabilities in general, let alone students with visual impairments (Miller & Mercer, 1997;National Mathematics Advisory Panel, 2008;Sprick, 1987). Dick and Kubiak (1997) argued that many students with visual impairment may not have access to Braille textbooks or they may not be fluent in Braille. Further, if the school changes textbooks or editions, students may not have immediate access since translating a book into Braille takes time (Dick & Kubiak).…”
mentioning
confidence: 99%
“…Second, more research is needed to develop effective instructional strategies to teach math to students with severe visual impairments and increase their achievement level, particularly at the higher levels of math. Recent publications have addressed math instruction for this group of students (Dick & Kubiak, 1997;Kapperman, Heinze, & Stricken, 1997;Kapperman & Stricken, 1998;Liedke, 1998), but more research is needed at all levels of math.…”
Section: Recommendationsmentioning
confidence: 99%
“…The buttons on traditional calculators are often small in order to make calculators handheld (Tech Connections, 2004). Additionally, the typical LCD screen on mass marketed calculators produces small numbers and offers minimal contrast between the numbers and the background (Dick & Kubiak, 1997;Tech Connections, 2004). To address these limitations, companies and researchers have developed adaptive or accessible calculators.…”
Section: Calculatorsmentioning
confidence: 99%